Black Academic Scholarship Fund (BASF) and Education - Gaining Equity in Education and Empowering Black Learners - Piggott, Sylivia E. A. (Collaborative Unity and Existential Responsibility, 2019)
This article explains the movement for Africentric public schools in Canada, particularly in Montreal, and the controversy it has generated. It is also argued that Black youth would gain significantly from community based educational programs that root their learning more closely in the life, experiences and needs of their community.

Black and English-speaking in Montreal : an Intersectional Snapshot - Zehavi, Bonnie (Collaborative Unity and Existential Responsibility, 2019)
This paper presents a general overview of the challenges faced by English-speaking Black community members in Montreal, as well as the exacerbation of those barriers for individuals with a history of justice involvement. Frontline community initiatives focusing on education, employment, and entrepreneurship at DESTA Black Youth Network are profiled as an example of grassroots efforts to mitigate disparate circumstances between English-speaking Black Montrealers and their white counterparts. Statistical data in the areas of educational attainment, rates of unemployment, and income provide the platform for analysis and, recognizing the multiple identity experiences of belonging to a racialized and linguistic minority, an intersectional framework is employed. Recommendations for more race-based study, policy, and funding to better support equity strategies are provided.
Keywords: Official Language Minority Community (OLMC)

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (Collaborative Unity and Existential Responsibility, 2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2019)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2019)

Semaji - Black Community Resource Centre (BCRC) (2019)

Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities, 2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

The Black Community Resource Guide 2010/2011 - Black Community Resource Centre (BCRC) (2011)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)